A Multi-source Investigation of Issues Arising from the Implementation and Evolution of a Commercial, Non-medical Cannabis Market in Colorado - Subritzky, Todd (Curtin University, 2019)
In 2012 Colorado legalised a commercial cannabis market for pleasure, in 2014 becoming the world’s first fully commercialised cannabis market. This thesis analysed media, documentary and key informant sources to examine macro and micro issues arising from the implementation and evolution of the market. It provided early qualitative insights from the pre-implementation phase and the first five years post implementation. The research was conducted primarily from a harm reduction perspective and included evidenced based recommendations.